2004
DOI: 10.1111/j.1439-0329.2004.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

PCR‐based identification of Erysiphe pulchra and Phyllactinia guttata from Cornus florida using ITS‐specific primers

Abstract: SummaryThe internal transcribed spacer (ITS) regions of rDNA and the intervening 5.8S rRNA gene for the powdery mildew fungi Erysiphe (sect. Microsphaera) pulchra and Phyllactinia guttata were amplified using standard polymerase chain reaction (PCR) protocols and the universal primer pairs, ITS 1 and ITS 4 . PCR products for ITS were analysed by electrophoresis in a 1.5% agarose gel and sequenced. The size of the amplified ITS products (approximately 650 bp) were not sufficiently different to allow reliable di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
0
8
2
Order By: Relevance
“…Therefore, the classical morphological criteria and host range data used in identification (Braun et al., 2002) can now be supplemented with molecular methods. Although two ITS primer pairs that distinguished E. pulchra from P. guttata at the anamorph stage have been reported (Mmbaga et al., 2004), our further studies showed the two identified ITS primer pairs were not species‐specific for the two pathogens. The objective of the present work was to develop species‐specific primers for easy detecting and distinguishing the two fungi, P. guttata and E. pulchra causing powdery mildews in dogwood.…”
Section: Introductioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Therefore, the classical morphological criteria and host range data used in identification (Braun et al., 2002) can now be supplemented with molecular methods. Although two ITS primer pairs that distinguished E. pulchra from P. guttata at the anamorph stage have been reported (Mmbaga et al., 2004), our further studies showed the two identified ITS primer pairs were not species‐specific for the two pathogens. The objective of the present work was to develop species‐specific primers for easy detecting and distinguishing the two fungi, P. guttata and E. pulchra causing powdery mildews in dogwood.…”
Section: Introductioncontrasting
confidence: 62%
“…Considering the limitations of small sample sizes, this specific detection method will be further evaluated on a large scale to survey P. guttata and E. pulchra in dogwood. Previously reported ITS primers for E. pulchra , EP1/EP2 and for P. guttata , PG1/PG2 (Mmbaga et al., 2004) did not produce unique PCR band for E. pulchra or P. guttata . The reason may be that the primer EP1 was not a specific primer to E. pulchra and its sequence can be found in other organisms such as Adenia mannii or Phellinus robiniae .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…For the Phyllactinia species, the PG 1 /PG 2 primers already described in the literature (Mmbaga et al, 2004) for the amplification of P. guttata from Cornus were used, since we checked from sequence alignments that they could amplify the sequence of Phyllactinia obtained in our previous study (Mougou et al, 2008). For the Erysiphe species, the three ITS sequences corresponding to E. alphitoides, E. hypophylla and E. quercicola were aligned, and the PRIMER 3 software (Rozen and Skaletsky, 2000) was used to design primer sets in the variable regions.…”
Section: Detection Of Oak Powdery Mildew Its Typesmentioning
confidence: 99%